2023
DOI: 10.3390/su152215999
|View full text |Cite
|
Sign up to set email alerts
|

Drought Assessment in Greece Using SPI and ERA5 Climate Reanalysis Data

Ioannis M. Kourtis,
Harris Vangelis,
Dimitris Tigkas
et al.

Abstract: The present work aims to assess the spatial variability and the trends of the annual rainfall and meteorological drought in the entire territory of Greece utilising the ERA5 reanalysis precipitation dataset of the European Centre for Medium-Range Weather Forecasts (ECMWF), which spans from January 1940 to December 2022 (an 83-year period). Drought assessment took place based on the Standardized Precipitation Index (SPI) for timescales ranging from 1 month to 12 months. Evaluation was carried out by calculating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 99 publications
2
0
0
Order By: Relevance
“…Karavitis et al [76] showed that 1989-1990 was indeed one of the driest years throughout Greece. The same pattern is validated from other similar studies [5,77]. Vasiliades [78] revealed that the hydrological year 1976-1977 was the driest recorded year, whereas the second one was 1989-1990, which was characterized as a severe drought event.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Karavitis et al [76] showed that 1989-1990 was indeed one of the driest years throughout Greece. The same pattern is validated from other similar studies [5,77]. Vasiliades [78] revealed that the hydrological year 1976-1977 was the driest recorded year, whereas the second one was 1989-1990, which was characterized as a severe drought event.…”
Section: Discussionsupporting
confidence: 85%
“…In contrast, the wettest year (2002)(2003) showed very wet conditions prevailing in many parts of the study area. This is also validated by Kourtis et al [77]. A previous study using the Reconnaissance Drought Index (RDI) is also in accordance with the previous assumption [78].…”
Section: Discussionsupporting
confidence: 85%